2021
DOI: 10.1002/jhbp.964
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification and goal of systemic therapy for successful surgical management of colorectal liver metastases: Oncological optimization

Abstract: For patients with stage IV colorectal cancer (CRC), curative‐intent surgery has actively been performed for expecting prolonged survival outcomes. However, because the population with stage IV CRC is considerably heterogeneous, optimal selection of surgical candidate is inevitable to maximize survival outcomes. In the era of effective chemotherapy, there is an increasing need for a strategic use of chemotherapy as a part of multidisciplinary treatment to expand surgical indications and enhance the clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Liver metastasis is no longer a contraindication of surgery for colorectal cancer [3]. Resection of a limited number of liver metastases is reported as beneficial for improving the prognosis of patients with CRC [28]. In our study, although liver metastasis was generally observed to occur in the CRC lesions without mucus or SRCC, which always had intense 18 F-FDG uptake, some small liver metastases were missed by 18 F-FDG PET/CT, similar to the report by Maffione AM [29].…”
Section: Discussionmentioning
confidence: 99%
“…Liver metastasis is no longer a contraindication of surgery for colorectal cancer [3]. Resection of a limited number of liver metastases is reported as beneficial for improving the prognosis of patients with CRC [28]. In our study, although liver metastasis was generally observed to occur in the CRC lesions without mucus or SRCC, which always had intense 18 F-FDG uptake, some small liver metastases were missed by 18 F-FDG PET/CT, similar to the report by Maffione AM [29].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic relevance of LDT for LM from certain malignancies, such as colorectal cancer, has already been established [ 7 - 9 ]. In such tumors, LDT can achieve good local disease control, and even a cure in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chemotherapy is generally considered to be the standard treatment for hepatic recurrence following EC resection, but its prognostic relevance is limited, with a reported median post-recurrence survival of only 7 months [ 6 ]. For other malignancies (e.g., colorectal carcinoma), liver-directed therapy (LDT), which includes surgical resection, irradiation and radiofrequency ablation (RFA), is regarded as being effective, and possibly even a curative strategy for liver recurrence [ 7 - 9 ]. However, the role of liver-focused management for hepatic recurrence of EC remains poorly understood [ 9 ], and thus merits further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…(17,18) Even though various clinical trials serve as evidence to guide our clinical practice, the clinical decision making is actually complex and heavily dependent on the conditional probability based on the reported data and our experiences. (16) As such, a multidisciplinary team approach is important to take the appropriate path, avoiding unnecessary/inefficient ways, for maximizing the survival outcomes of patients with advanced hepatic malignancies.…”
Section: Clinical Decision and Fate Of A Patient With Hepatic Malignancymentioning
confidence: 99%